PERLINDUNGAN DATA ANAK TERHADAP PENYALAHGUNAAN DI PLATFORM DIGITAL: ANALISIS HUKUM DAN KEBIJAKAN - Mhd. Sanip Heri Sinaga; Rahmayanti (Smart Education, 2026)
The protection of children's data on social media is an issue that requires serious attention from various parties in order to prevent various negative impacts on users, especially children. This research uses a normative legal research method. The results of the study indicate that forms of misuse of children's data on digital platforms, such as excessive data collection, data mining and profiling, sale of data to third parties, targeted advertising, and identity theft, demonstrate that children's digital activities can pose serious threats to their privacy rights and security. Legal regulations and prevention of misuse of children's data have been regulated under Law Number 27 of 2022 concerning Personal Data Protection. However, the regulation still has several weaknesses, such as the absence of detailed provisions regarding the special processing of children's data. Effective legal policies to protect children's personal data require specific regulations or implementing rules that comprehensively regulate the collection, use, and storage of children's personal data. The processing of children's personal data must also involve verified consent from parents or legal guardians, along with active government supervision to prevent data misuse. In addition, every digital platform is required to implement strong cybersecurity standards to protect children's personal data from data breaches and illegal access.